Clinical-epidemiological characteristics of patients with multiple sclerosis in two high complexity hospitals - Delgado-Cabrera, Richard (2021)
Objetive: To know the clinical-epidemiological characteristics of patients with multiple sclerosis of two high complexity hospitals in the Lambayeque region between 2012-2017. Material and methods. reviewed 84 medical records of patients diagnosed with multiple sclerosis at Almanzor Aguinaga Asenjo National Hospital and Lambayeque Regional Hospital. The data obtained were recorded in a data collection sheet composed of 17 items. We worked with the database in SPSS v 22, for the descriptive analysis we used absolute and relative frequency. Results: The most common form of presentation was the progressive primary form, with an average age of 44 years; among the most frequent clinical manifestations, limb weakness was found, followed by retro ocular pain. The total number of patients diagnosed with multiple sclerosis was performed, nuclear magnetic resonance as a diagnostic test. Conclusions: The most frequent clinical manifestations were weakness of upper and lower limbs, retro ocular pain, paraesthesia, ataxia and fatigue. They were mostly men with an average age of 44 years. Most of them came from the coast and had no infections prior to diagnosis. Magnetic resonance imaging was performed as a complementary test in all patients.